Conversion of Waste Cooking Oil into Bio-Fuel via Pyrolysis Using Activated Carbon as a Catalyst - Warintorn Banchapattanasakda; Channarong Asavatesanupap; Malee Santikunaporn (Molecules, 2023)
The utilization of activated carbon (AC) as a catalyst for a lab-scale pyrolysis process to convert waste cooking oil (WCO) into more valuable hydrocarbon fuels is described. The pyrolysis process was performed with WCO and AC in an oxygen-free batch reactor at room pressure. The effects of process temperature and activated carbon dosage (the AC to WCO ratio) on the yield and composition are discussed systematically. The direct pyrolysis experimental results showed that WCO pyrolyzed at 425 °C yielded 81.7 wt.% bio-oil. When AC was used as a catalyst, a temperature of 400 °C and 1:40 AC:WCO ratio were the optimum conditions for the maximum hydrocarbon bio-oil yield of 83.5 and diesel-like fuel of 45 wt.%, investigated by boiling point distribution. Compared to bio-diesel and diesel properties, bio-oil has a high calorific value (40.20 kJ/g) and a density of 899 kg/m3, which are within the bio-diesel standard range, thus demonstrating its potential use as a liquid bio-fuel after certain upgradation processes. The study revealed that the optimum AC dosage promoted the thermal cracking of WCO at a reduced process temperature with a higher yield and improved quality compared to noncatalytic bio-oil.